Export performance cluster analysis of Poland’s regions in the first 20 years of EU membership - Umiński, Stanisław (Quaestiones Geographicae, 2025)
This paper analyses the evolution of Poland’s foreign trade (FT) at the regional (NUTS-2) level during the country’s first 20 years of European Union (EU) membership. The goal is to uncover region-specific export dynamics and structural adjustments that are often masked by national-level aggregates. We focus on export quality and structure, intra-industry trade (IIT) intensity, and the role of foreign-owned entities (FOEs). A novel contribution lies in our application of cluster analysis to dynamic export changes over time, rather than to static cross-sectional levels typically used in the literature. Using Ward’s agglomerative method, we identify six distinct regional clusters that capture heterogeneous trajectories of export transformation. While EU membership fostered expansion into the EU single market, it also served as a catalyst for diversification into non-EU markets, revealing Poland’s increasing global trade competitiveness. This approach reveals a strong degree of regional idiosyncrasy despite increasing national openness and EU integration. Our findings provide new insights for policymakers seeking to design regionally differentiated export support strategies.